The Santangelos - Collins, Jackie (St. Martin's Press, 2015)
"Legendary mega-seller Jackie Collins chronicles passion and power in one of America's most glamorous families. A vicious hit. A vengeful enemy. A drug addled Colombian club owner. A sex crazed Italian family. And the ever powerful Lucky Santangelo has to deal with them all, while Max--her teenage daughter is becoming The "It" girl in Europe's modeling world. And her Kennedyesque son, Bobby, is being set up for a murder he didn't commit. But Lucky can deal. Always strong and unpredictable with her husband, Lennie, by her side she lives up to the family motto--Never fuck with a Santangelo. Lucky rules. The Santangelos always come out on top. An epic family saga filled with love, lust, revenge and passion"--